1998
DOI: 10.1074/jbc.273.39.24992
|View full text |Cite
|
Sign up to set email alerts
|

Kinetic Analysis of the Mechanism and Specificity of Protein-disulfide Isomerase Using Fluorescence-quenched Peptides

Abstract: Protein-disulfide isomerase (PDI) is an abundant folding catalyst in the endoplasmic reticulum of eukaryotic cells. PDI introduces disulfide bonds into newly synthesized proteins and catalyzes disulfide bond isomerizations. We have synthesized a library of disulfide-linked fluorescence-quenched peptides, individually linked to resin beads, for two purposes: 1) to probe PDI specificity, and 2) to identify simple, sensitive peptide substrates of PDI. Using this library, beads that became rapidly fluorescent by r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

1999
1999
2017
2017

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 43 publications
0
17
0
Order By: Relevance
“…PDI, like some other folding assistants (47), must interact with a large number of different substrates with few recognizable sequence cues except for a small preference for peptides that contain cysteine (10,11). Recently, Winther and colleagues (13) found that peptide sequence can affect the rate at which PDI reacts with peptide disulfides with some preference for a sequence that has the features, small/helix breaker-Cys-X-hydrophobic/basic-hydrophobic. Peptide binding sites have been difficult to localize on PDI.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…PDI, like some other folding assistants (47), must interact with a large number of different substrates with few recognizable sequence cues except for a small preference for peptides that contain cysteine (10,11). Recently, Winther and colleagues (13) found that peptide sequence can affect the rate at which PDI reacts with peptide disulfides with some preference for a sequence that has the features, small/helix breaker-Cys-X-hydrophobic/basic-hydrophobic. Peptide binding sites have been difficult to localize on PDI.…”
Section: Resultsmentioning
confidence: 99%
“…PDI interacts covalently with substrate cysteines (9), but it also binds a variety of peptide/protein substrates (10). There are few strict sequence/structure requirements for binding (11,12), although there is some effect of sequence on reactivity with PDI (13). PDI activity can be inhibited by a number of peptides (11), including the cyclic peptide antibiotic, bacitracin (14,15).…”
Section: Protein Disulfide Isomerase (Pdi)mentioning
confidence: 99%
“…15 N, 2 H labeling of the protein was obtained by expressing it in 0.5 liters of M9 minimal medium supplemented with 1 g Celtone dN powder (Martek Biosciences, Columbia, MD) and 2 g͞liter glucose. Recombinant human PDI was expressed and purified as described (10), except for an additional, final purification step on a Superdex 200 gelfiltration column (Amersham Pharmacia). For the recombinant expression of human ERp57 we used Escherichia coli BL21(DE3) cells freshly transformed with the pHisERp57 expression vector, which encodes a N-terminal 22-aa affinity tag containing a deca-histidine sequence and a factor X a cleavage site.…”
Section: Methodsmentioning
confidence: 99%
“…2). Although GSSG is not a substrate for which PDI exhibits a high affinity, it is one of the smallest and more important substrates of PDI (59). The role of this enzyme in controlling the GSH/GSSG buffer has been a subject of research in the near past (13,26,60).…”
Section: Gsh/gssg Buffer In Catalysis By Hpdimentioning
confidence: 99%